2011
DOI: 10.1093/cid/ciq164
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguous Nucleotide Calls From Population-based Sequencing of HIV-1 are a Marker for Viral Diversity and the Age of Infection

Abstract: The fraction of ambiguous nucleotide calls in bulk sequencing of human immunodeficiency virus type 1 (HIV-1) carries important information on viral diversity and the age of infection. In particular, a fraction of ambiguous nucleotides of >.5% provides evidence against a recent infection event <1 year ago.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
166
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(180 citation statements)
references
References 18 publications
12
166
1
1
Order By: Relevance
“…Because of the retrospective nature of our analysis, two different PCR systems, sequencing systems, and software packages to call ambiguous bases were used over time, which is an inherent technical limitation of the SAM. However, the methodological diversity in our study was still lower than in related studies (14)(15)(16). Since Ragonnet-Cronin et al (15) demonstrated that differences in ambiguous base calling were at least negligible in the commonly used threshold range of 15 to 25%, we consider the sequencing software to have only a minor influence on the overall frequency of ambiguous base calling.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Because of the retrospective nature of our analysis, two different PCR systems, sequencing systems, and software packages to call ambiguous bases were used over time, which is an inherent technical limitation of the SAM. However, the methodological diversity in our study was still lower than in related studies (14)(15)(16). Since Ragonnet-Cronin et al (15) demonstrated that differences in ambiguous base calling were at least negligible in the commonly used threshold range of 15 to 25%, we consider the sequencing software to have only a minor influence on the overall frequency of ambiguous base calling.…”
Section: Discussionmentioning
confidence: 60%
“…In the previous studies, sequence ambiguity thresholds of 0.45% (15), 0.47% (16), and 0.5% (14) were described to best identify infections acquired within Յ155 days (15) or Յ365 days (14, 16) with accuracies of 79.9% (15), 79.7% (16), and 70.9% (14). Our analysis is in accordance with these reports, yielding a sequence ambiguity threshold of 0.5%, a mean duration of recency of 208 days, and an accuracy of 76.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this protocol, patients are offered early ART. After 1 y of suppressed viremia (,40 HIV-1 RNA copies/ ml plasma), patients can chose to interrupt ART (14)(15)(16)(17)(18). Study details are listed under http://www.clinicaltrials.gov; ID NCT00537966.…”
Section: Study Populationmentioning
confidence: 99%
“…A variety of methods for assessing HIV diversity are being explored as tools for estimating HIV incidence, including the quantification of ambiguous nucleotide calls and other computational approaches based on analyses of data from traditional or next-generation sequencing (13,14). We recently developed an assay that quantifies the level of genetic diversity in HIV populations without the use of sequencing (12,15).…”
mentioning
confidence: 99%